What Regulatory Problems Arise When Fintech Lending Expands into Fledgling Credit Markets? - Jonathan Greenacre (Washington University Journal of Law & Policy, 2020)
This article argues that when moving into fledgling credit markets – namely communities in which a significant portion of the population has never had access to formal consumer loans – fintech lending can cause significant adverse economic consequences to the public and create significant regulatory gaps that require addressing. These economic consequences include inaccurate risk-pricing as firms determine how to accurately process and use the range of information at their disposal, as well as, potential behavioral problems leading to widespread default as members of low-income communities, particularly those without a bank account (the so-called ‘unbanked’), access formal credit for the first time. Regulatory gaps emerge because intellectual silos continue to focus on consumer credit emerging from the banking sector, not fintech. This article focuses on the spread of fintech lending in Kenya since 2012 as a case study for its broader argument and examines potential starting points for developing regulatory frameworks for fintech lending.
Keywords: fintech; financial; financial services; financial technology; finance; finance law; law; technology law; consumer; credit; lending